Cast netting new species: Integrative taxonomy of Distichodus notospilus (Characiformes: Distichodontidae) discovers new species and overlooked areas of endemism in Central Africa - Schmidt, Ray C.; Knobloch, Elise C.; Barrientos, Christian (Zootaxa, 2021)
Distichodus notospilus was described from the Ogooué River and is considered to occur throughout the Lower Guinea ichthyofaunal province and the western tributaries of the middle and lower Congo River. Recent expeditions in Equatorial Guinea collected D. notospilus specimens in the Mbini River drainage and the Mbia River; a small coastal river that is located between the Ntem and Mbini river drainages. Detailed morphological analyses and multilocus molecular analyses confirm that these two populations are distinct from one another. Topotypic populations of D. notospilus were included in the analyses and demonstrated that populations in the Mbini and Mbia rivers are distinct and these two new species are described herein. Distichodus microps sp. nov. is endemic to the Mbia River drainage and is distinguished from D. notospilus in having more scales along the lateral line (41, rarely 40 versus 37–39, rarely 40), a nearly inferior mouth versus subterminal in D. notospilus, a curved posterolateral margin of the opercle versus straight in D. notospilus, a smaller eye (56.7–80.4 versus 70.1–104.3 % of snout length), and a less prominent elongated spot at the base of the caudal fin. Distichodus mbiniensis sp. nov. is endemic to the upper Mbini River drainage and distinguished from D. notospilus in having more scales along the lateral line (41–42, rarely 40 versus 37–39, rarely 40), a much less prominent elongated dark spot at the base of the caudal fin, and a shorter dorsal fin (21.4–27.2 versus 22.7–34.2% standard length). Distichodus microps is distinguished from D. mbiniensis in having a shallower body (usually six scales from lateral line to the pelvic fin versus seven), fewer anal-fin rays (usually 12 total rays versus 13 or 14), a more inferior mouth, a deeper and longer caudal peduncle, a smaller eye, and differences in several features associated with the head. In addition to the two new species described this study also revealed potential undescribed diversity in the D. notospilus species complex in the Ntem River and Dja River (Congo R. basin) in Cameroon. The biogeography of these fishes in the rivers of Lower Guinea suggests that the Mbini River and smaller coastal rivers are overlooked areas of endemism. Studies of other reported widespread species will likely reveal additional diversity and further elucidate the processes promoting and maintaining freshwater diversity in Central Africa.